2018
DOI: 10.1002/etep.2636
|View full text |Cite
|
Sign up to set email alerts
|

Grid-connected converter control during unbalanced grid conditions based on delay signal cancellation

Abstract: Summary Considering the recent trend in energy sector transformation towards high share of renewable energy sources, it has become very hard to imagine modern power system without the integration of power electronic devices. A grid‐connected converter will be on the forefront of future energy trading, while simultaneously striving to offer good dynamic behaviour and operation in full accordance with the relevant grid requirements. The control algorithm of the grid‐connected converter has to be capable of achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…By substituting the proposed controller (14), (15), (21) and (22) into the system dynamics (4) and (5), the closed-loop system takes the form…”
Section: Current-limiting Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…By substituting the proposed controller (14), (15), (21) and (22) into the system dynamics (4) and (5), the closed-loop system takes the form…”
Section: Current-limiting Propertymentioning
confidence: 99%
“…The way current limitation is achieved under unbalanced grid conditions still represents a challenging task, especially when droop controlled inverters are considered, since their task is to regulate the grid voltage and frequency. The authors in [6,21] have implemented controllers that ensure a balanced current provision under voltage sags. As explained in [6], this enhances the fault-ride-through capability in terms of injecting only positive sequence powers/current that comply with the FRT requirement, while current limitation at the steady-state is achieved through the controller reference powers.…”
Section: Introductionmentioning
confidence: 99%
“…Separation of positive and negative sequence current components was proposed as a solution of nonfixed control variables . In recent papers, improvement of this method was described, like delay signal cancellation in the negative sequence reference frame for the mitigation of negative sequence currents . Nevertheless, even if applied, sequence decomposition‐based methods generally assume symmetrical current target, which is not fully beneficial for the grid either in the inverter or the rectifier operation mode.…”
Section: Introductionmentioning
confidence: 99%
“…A delayed signal cancelation method has been introduced to improve the conventional PLL performance. However, the enhanced performance is achieved at the cost of increased complexity and computational burden . Generalized integrator (GI)–based method has been explored recently and found effective to deal with weak‐grid scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…However, the enhanced performance is achieved at the cost of increased complexity and computational burden. 20 Generalized integrator (GI)-based method has been explored recently and found effective to deal with weak-grid scenarios. A second order GI is reported in another research 21 for distortion rejection; however, they have been found ineffective in dealing with dominant lower order harmonics and DC offset.…”
Section: Introductionmentioning
confidence: 99%